2008
DOI: 10.1017/s000711450803081x
|View full text |Cite
|
Sign up to set email alerts
|

Absorption, metabolism and excretion of flavanones from single portions of orange fruit and juice and effects of anthropometric variables and contraceptive pill use on flavanone excretion

Abstract: Oranges are rich sources of flavonoids that are bioactive and may protect against age-related diseases. The absorption of orange flavanones may be affected by factors such as processing and subject anthropometric variables, and the bioactivity of the absorbed phytochemicals depends on how they are metabolised during absorption. In a randomised cross-over study, twenty subjects consumed a single portion of orange fruit (150 g) or juice (300 g) that contained the flavanones narirutin and hesperidin, and an addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
165
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(182 citation statements)
references
References 51 publications
16
165
1
Order By: Relevance
“…The authors argued that the kidney may be involved in postabsorption phase II metabolism, which could be explained by the expression of SULT1A1 in the kidneys (Meinl et al, 2006;Riches et al, 2009), the enzyme for which we found a high affinity toward hesperetin resulting in sulfonation at very low concentrations. In a third study in which human volunteers were given oranges or orange juice providing, respectively, 161 or 145 mg of hesperidin, hesperetin 7-O-glucuronide and 3Ј-Oglucuronide were detected in blood and plasma, as well as hesperetin 3Ј-O-sulfate, as qualified by liquid chromatographytandem mass spectrometry and metal complexation techniques (Brett et al, 2009). The absence of hesperetin 7-O-sulfate in these human volunteers is supported by the sulfonation kinetics found in the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors argued that the kidney may be involved in postabsorption phase II metabolism, which could be explained by the expression of SULT1A1 in the kidneys (Meinl et al, 2006;Riches et al, 2009), the enzyme for which we found a high affinity toward hesperetin resulting in sulfonation at very low concentrations. In a third study in which human volunteers were given oranges or orange juice providing, respectively, 161 or 145 mg of hesperidin, hesperetin 7-O-glucuronide and 3Ј-Oglucuronide were detected in blood and plasma, as well as hesperetin 3Ј-O-sulfate, as qualified by liquid chromatographytandem mass spectrometry and metal complexation techniques (Brett et al, 2009). The absence of hesperetin 7-O-sulfate in these human volunteers is supported by the sulfonation kinetics found in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of metabolites in plasma demonstrated the existence of other glucuronide and sulfo-conjugates as well (Matsumoto et al, 2004;Mullen et al, 2008;Brett et al, 2009). Different individual UGTs and SULTs probably possess different kinetics and regioselectivity for the conjugation of hesperetin, as has been reported for the glucuronidation and sulfonation of other flavonoids (Boersma et al, 2002;Otake et al, 2002;Zhang et al, 2007a;Tang et al, 2009), and, therefore, different levels of expression of UGTs and SULTs might lead to different metabolite patterns.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Wang et al (2006) found that rat intestinal microsomal CL int , V max , and K m values for glucuronidation of the isoflavones were unrelated to rates of glucuronidation in an intestinal perfusion model. Data from clinical trials of flavonoid metabolism using a wide range of ages are lacking, but interestingly, in a study of 129 subjects consuming orange juice, urinary excretion of hesperetin was decreased with advanced age, equating to a 4% decrease between the ages of 20 and 80 years (Brett et al, 2009). Although the mechanism of the decrease in urinary excretion remains to be explored, age could be considered as a potential, albeit weak, modifier of flavonoid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Even though flavonoids have been intensively studied for decades [59], surprisingly there are only limited number of in vivo studies available that provide these data [12]. In most studies, flavonoid conjugates in plasma were identified and quantified from the amounts of aglycone liberated from conjugated metabolites by using β-glucuronidase and sulfatase to deconjugate the conjugated metabolites to their respective aglycone [60][61][62][63][64][65][66][67][68]. This method has been criticized for running a risk of underestimation and lack of information on the absolute structural conformation of flavonoid conjugates especially with respect to the conjugation position [60,61].…”
Section: Quality Of In Vivo Data On Metabolic Patterns In Plasma For mentioning
confidence: 99%